Analyzing The Bounce And Pitch Phenomenon Of Vehicle Model Through Xzbm Algorithm - Karmiadji, Djoko W (Universitas Muhammadiyah Yogyakarta, 2005)
In general, a vehicle model is one having multiple bodies, with each body being supported on a suspension represented by the tires, springs, and damping devices. The components of rigid body motion contain displacements, velocities, and accelerations at the body center of mass. These components consist of translation and rotation in and about the orthogonal axis directions. Since the springs and dampers have the steady loading due to the sprung body, the steady state of the model can be determined. The vertical bounce and pitch responds are influenced by the stiffness of dampers, springs and tires. The pure bounce is represented by the vertical response and the pitch motion is represented by the rotation at its rotation center. This paper demonstrates the bounce and pitch phenomenon through the benchmark model of vehicle, which is analyzed for determining the equilibrium state. The equations for bounce and pitch plane motions representing the X-Z multibody system are established by using the XZBM algorithm. The vehicle parameters are used for the numerical computations which the analysis established the bounce and pitch conditions